Nitrogen removal from piggery waste with anaerobic pretreatment - Kim, D H (Water science and technology : a journal of the International Association on Water Pollution Research, 2004)
Aerobic degradation of high strength piggery waste elevated the reactor temperature inhibiting nitrification. This study included anaerobic pretreatment with various influent by-pass rates to control the temperature and to minimize the external carbon requirement for denitrification. To find the optimum operating conditions, both lab-scale AnSBR (anaerobic sequencing batch reactor) and Ax/Ox (anoxic/oxic) SBR were operated at 35 degrees C. The heat energy released from Ax/Ox SBR was assumed to be used for heating the AnSBR, with which the Ax/Ox reactor temperature could successfully be controlled below 40 degrees C. The optimum rates of by-pass were 1.0 for winter, 0.4 for spring/fall and 0.2-0.4 for summer, respectively. Applying the correction factors for the measured AUR2 (nitrite nitrification rate) and AUR (nitrate nitrification) at the predicted temperatures, the required oxic HRTs were computed. The required Ax/Ox HRT ratios were respectively 0.5 for COD/TKN>8, 1.0 for COD/TKN ratio of 5.5-8 and 3.5 for below 5.5. The optimum HRTs were 16 days for AnSBR and 17 days for Ax/Ox SBR with the corrected AUR2